Chest Trauma Evaluation and Outcome of Management in a Tertiary Hospital-One Year Experience - Islam, Md Mahmudul; Azad, Khondkar A K; Islam, Md Aminul; Chakraborty, Rivu Raj (Journal of Surgical Sciences, 2020)
Background: Chest trauma is responsible for 50% of deaths due to trauma. This kind of death usually occurs immediately after trauma. Various therapeutic options have been reported for management of chest injuries like clinical observation, thoracocentesis, tube thoracostomy and open thoracotomy. Methods: This is an observational study carried out in the department of Casualty, Chittagong Medical College Hospital over a period of one year (from April 2015 to March 2016). All the patients (both male and female) admitted in the casualty units within the specified period were included in this study. Result: The mean age was found 37.7±18.1 years and male-female ratio was 11.8:1. Almost one third (35.7%) patients were affected by road traffic accident. 42(27.2%) patients were found open pneumothorax followed by rib fracture-41(26.6%), haemopneumothorax-31(20.1%), pneumothorax- 14(9%), haemothorax-12(7.8%), chest wall injury-6(3.9%), tension pneumothorax-5(3.2%), and flail chest-3(1.9%). More than three fourth (80.5%) patients were managed by tube thoracostomy followed by 28(18.2%) observation and 2(1.3%) ventilatory support. No thoracotomy was done in emergency department. Re-insertion of ICT was done in 6(4.7%) patients. More than two third (68.2%) patients recovered well, 43(27.9%) patients developed complications and 6(3.9%) patients died. Conclusion: Most of the patients were in 3rd decade with male predominance. Road traffic accident was the commonest cause and open pneumothorax was the commonest chest trauma. Three-fourths were managed by tube thoracostomy. Nearly one third of the patients had developed complications and about four percent of patients died. Journal of Surgical Sciences (2019) Vol. 23 (1) : 19-24